Cognitive Semantics of Social Media Themed Proverbs in Generation Z Interactions - Mega Williandani; Mulyadi Mulyadi (RIRAI Publisher, 2023)
Proverbs are an important aspect of language and culture that are used to describe meanings, experiences and values that are common across cultures. This article explores social media-themed proverbs that reflect Generation Z's interactions in daily life. This generation, growing up in the age of technology, views life through the lens of social media, and the proverbs expressed reflect their views on popularity, transient life, and the reality behind the online filter. By delving into proverbs such as